Triglyceride lowering LPL alleles combined with LDL-C lowering alleles are associated with an additively improved lipoprotein profile - Christodoulides, C (Elsevier, 2021)
Aim and objectives: In Mendelian Randomization studies, triglyceride (TG) lowering lipoprotein lipase (LPL) alleles and LDL-cholesterol (LDL-C) lowering alleles have shown additional beneficial associations with cardiovascular disease (CVD) risk. We aimed to provide further insight in this observation by applying Mendelian Randomization analyses of genetically influenced TG and LDL-C levels on plasma metabolomic profiles.